Rancang Bangun Prototipe Sistem Start Engine dan Alarm Sepeda Motor Menggunakan Mikrokontroler Arduino Berbasis Android - Punaji Haruman; Joko Saputro; Asruddin Asruddin (Sistem Komputer & Teknologi Intelegensi Artifisial (SIKOMTIA), 2023)
The rapid development of information technology has had a significant impact on various fields, both through the use of electronics and mobile devices, as well as the easily developed Android operating system. However, the current vehicle security systems are still inadequate in ensuring the safety of vehicles, especially concerning criminal activities such as theft and robbery. To address this issue, the idea of implementing a telephone facility through research has emerged, aiming to design and create a prototype of a start engine and motorcycle alarm system using the Arduino microcontroller based on Android. The purpose of this research is to reduce the frequency of crimes that occur through tampering with vehicle contacts, with the expectation that the implementation of an improved security system will lead to a decrease in vehicle theft cases and provide better protection for vehicle owners.